Neighborhood Interest and Security Concerns in Nepal: A Geopolitical Perspective - Baral, Bhim Nath (Journal of Political Science, 2021)
Pedestaled on both descriptive and analytical data acquired from secondary sources, this article analyzes the interests of China and India, Nepal’s immediate neighbors. Their interest is examined from security point of view against the backdrop of increased Sino-Indian dynamics of competition in Nepal, using a geopolitical perspective. Security is the vital concept in the study of global politics. The world political dynamics is changing rapidly and security dimensions are also changing with it. Both China and India are trying to be the superpowers in the world. So, it is natural for them to influence regional and world politics in accordance of their own interest. In the present time, both of them are contesting to strengthen their position in Nepal due to their strategic position in the regional politics of South Asia. Nepal cannot remain isolated from the interest of immediate neighbors. Nepal’s geographical proximity to Tibetan Autonomous Region of China and the issue of Tibetan refugee heightened China’s security concerns in Nepal. India, on the other hand, has also remained highly concerned with the increasing Chinese engagement in Nepal as India and Nepal share a long and open border contingent with the 1950 Treaty of Peace and Friendship. In this context of trilateral quandary, it is necessary to balance the China-India paradox because both are equally important for Nepal's security, peace and development.